2018
DOI: 10.7179/psri_2018.32.05
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes de padres e hijos hacia un ocio compartido en familia

Abstract: FINANCIACIÓN: El texto que presentamos se vincula al Proyecto de Investigación "De los tiempos educativos a los tiempos sociales: la cotidianidad familiar en la construcción del ocio físico-deportivo juvenil" (EDU2012-39080-C07-05), y configura los inicios del proyecto de I+D+I "Ocio y bienestar en clave intergeneracional: de la cotidianidad familiar a la innovación social en las redes abuelos-nietos" (EDU2017-85642-R); ambos cofinanciados en el marco del Plan Nacional I+D+I con cargo a dos ayudas del Minister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
1
4
0
20
Order By: Relevance
“…Regarding the family sphere, this study shows that young people do share leisure activities with their families, which is consistent with previous research (Ponce de León et al, 2015; Sanz et al, 2018) that verifies the desire to practice this type of leisure, but it disagrees with other authors (Berntsson and Ringsberg, 2014) who state that few young people acknowledge that they share their leisure experiences with direct relatives. This reveals a lack of agreement in the scientific literature on this issue.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regarding the family sphere, this study shows that young people do share leisure activities with their families, which is consistent with previous research (Ponce de León et al, 2015; Sanz et al, 2018) that verifies the desire to practice this type of leisure, but it disagrees with other authors (Berntsson and Ringsberg, 2014) who state that few young people acknowledge that they share their leisure experiences with direct relatives. This reveals a lack of agreement in the scientific literature on this issue.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, it is confirmed that the family is a privileged area for the construction of the children’s leisure (Valdemoros et al, 2014) and that family-shared leisure provides benefits for family functioning (Agate et al, 2009; Maynard and Harding, 2010; Craig and Mullan, 2012; Veenstra and Patterson, 2012; Grosso et al, 2013; Offer, 2013, 2014; Pinxten and Lievens, 2014; Sanz et al, 2018). The numerous benefits derived from leisure experiences when self-managed by young people are also shown (Ortega et al, 2015; Doistua and Ried, 2016; Doistua et al, 2016; Lazcano and Caballo, 2016).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…En el caso de la infancia, la confluencia de coordenadas temporales está marcada por las dinámicas familiares y por las relaciones que se establecen con los centros escolares (Fraguela, Lorenzo y Varela, 2011;Sintes, 2015;Varela et al, 2016); unas dinámicas en proceso de transformación, derivadas de los nuevos roles sociales y laborales de los padres/madres, de los diferentes estilos de vida, de la redefinición del papel de las familias (Buxarrais y Bruguet, 2014;Sanz et al, 2018), así como de los servicios socioeducativos disponibles en los contextos locales de proximidad (Caballo et al, 2012;Gradaílle y Varela, 2018).…”
Section: Conciliación Y Bienestar Infantilunclassified
“…Given the prominent role of the family in the construction of leisure habits and values, the challenge is to ensure both sufficient education on the part of parents and guardians in order to understand the value of leisure, and an environment that provides accessible, stimulating resources for all (Caballo et al, 2020;López, 2015;Varela & Maroñas, 2019). Shared family leisure time has also been shown to improve cohesion within the family, and promote skills and attitudes among young people that impact positively on their education and development (Kleiber, 1999;Offer, 2013;Sanz et al, 2018). Despite the benefits of leisure on the development of adolescents, lack of time (often associated with school workload) is a significant obstacle to leisure among young people in this age group, especially girls, who tend to devote more time to their studies than their male peers (Aciego & Domínguez, 1998;Madariaga & Romero, 2016).…”
Section: Introductionmentioning
confidence: 99%